THE USE OF CAD/CAM TECHNOLOGY IN SURGICAL TREATMENT OF CONDYLAR HEAD FRACTURE - Tetiana Pavlychuk; Denis Chernogorskyi; Yurii Chepurnyi; Andreas Neff; Andrii Kopchak (Bogomolets National Medical University, 2019)
Management of the condylar head fractures is still one of the most controversial issues of the maxillofacial surgery. The aim of the present study was to increase the accuracy and quality of the surgical treatment of condylar head fracture with the use of navigation surgical guide and patient specific reinforcement two-component plate and individualized fixator with the use of CAD/CAM technology. In study was included 8  patient with 10 condylar head fractured. In 5 cases was used navigation guides, in 4 cases (the biomechanical unfavorable)  was used the patient specific two-component plate and only in one case we used  individualized patient specific plate. A CT scan was done immediately after the operation. The reduction of the fragments and the location of the screws, plate and fixator were checked on the same view in the preoperative and postoperative pictures on the computer. The relation between the screw and the cortical bones was clearly shown on CT, and the sizes of the bicortical screws were suitable with no injury to the articular cartilage or surrounding tissue. The three-dimensional objects showed that the screw was in the designated position and the condyle had been replaced and fixed in the normal position. The height of the ramus on the fractured side was restored immediately postoperatively. The malocclusion was corrected and the passive mouth opening of each patient was never less than 3 cm. One  patients had transient paralysis of the temporal branch of the facial nerve postoperatively, which gradually recovered within a 2 month. Postoperative clinical examination showed good occlusion and mouth opening of at least 3 cm in all patients after 3 months without pain. All patients regained normal mandibular movements and had short and invisible scars at 6 months' follow-up. Given the small number of patients, this issue needs further study in randomized prospective studies involving more patients and evaluating long-term postoperative outcomes